(untitled) (American Journal of Islam and Society, 2016)
This catchy title, The Transnational Mosque, is timely and implies an analysis of global Islam and the multiplicities of mosque construction today. The premise promises to contribute to the scholarship on Islamic architecture, and yet there are some issues with the argument’s structure and even greater ones with the analytical depth with respect to architecture. The book’s structure highlights the attempt to separate itself and “builds upon” (p. 7) established texts on the subject of contemporary Islamic architecture. However, its relatively small format, dense with text, is populated sparely with uneven visual representation. The photographs vary in quality and vantage, and not all of the mosques discussed have images and architectural drawings – serious omissions in a field that is so visual, systematic comparative analysis requires analogous efforts with visual representation for the argument to sustain itself. The book contains an introduction; one chapter each on Turkey, Saudi Arabia, Iran, and the United Arab Emirates (UAE); and an epilogue that serves as a conclusion. But this four-fold argument, which focuses on the patron countries, is flawed because it inherently sets up a hierarchy of influence that situates equally the relatively minimal works of the UAE with the far-reaching impact of Turkey, Iran, and Saudi Arabia. It also ignores the “transnational” quality of those mosques not patronized by any of them. The introduction, “Agency of History: The Symbolic Potential for the Transnational Mosque,” begins with an italicized brief first-person narrative that describes Beirut’s Muhammad al-Amin Mosque followed by a long account of patronage and political climate. Rizvi promises an interdisciplinary approach with field work, architecture and photo documentation, interviews with architects and patrons in a “study [that] interrogates multiple agents and diverse agendas behind the construction of transnational mosques” (p. 5). She defines “trans” as “beyond and across time of history and spaces of nations,” but nevertheless frames the book in terms of nations ...